The Jews of Perpignan in the Thirteenth Century. an Economic Study Based on Notarial Records - Emery, Richard W. (Columbia University Press, 1959)
Uses the Notarial Register as a source of information on the economic history of the Jewish Community of Southern France during the 13th century